Airborne Remote Sensing of Wave Propagation in the Marginal Ice Zone. Issue 6 (28th June 2018) - Sutherland, Peter; Brozena, John; Rogers, W. Erick; Doble, Martin; Wadhams, Peter
Abstract: Airborne scanning lidar was used to measure the evolution of the surface wave field in the marginal ice zone (MIZ) during two separate wave events in the Beaufort Sea in October 2015. The lidar data consisted of a 2‐D field of surface elevation with horizontal resolutions between 17 and 33 cm, over a swath approximately 150‐220 m wide, centred on the ground track of the aircraft. Those data were used to compute directional wavenumber spectra of the surface wave field. Comparison with nearly collocated buoy data found the lidar and buoy measurements to be generally consistent. During the first event, waves traveling from open water into the ice were attenuated by the ice. The low spectral spreading and k 7 / 4 spectral dependence of the attenuation was consistent with dissipative models that treat sea ice as a highly viscous fluid floating on a less viscous ocean. Upper‐ocean eddy viscosities calculated using that model were found to be significantly lower than those from previous work. The second event was in off‐ice winds and cold temperatures, allowing measurement of the wave fetch relation in ice‐forming conditions. The wave growth rate was found to be slightly higher than previous measurements under unstable atmospheric conditions without ice formation. Comparison with WAVEWATCH III model output highlighted the importance of accurate ice information and fine geographic computational resolution when making predictions near the ice edge. Finally, the very short scales over which the wave field was observed to evolve in the MIZ are discussed. Key Points: Airborne scanning lidar provides directional wavenumber spectra of the rapidly evolving wave field in the MIZ Wave attenuation in thin pancake ice is predominately dissipative Wave growth rates in ice‐forming conditions are slightly higher than previous measurements under unstable atmospheric boundary layers